2010
DOI: 10.12702/1984-7033.v10n01a07
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability of soybean in terms of oil and protein

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
1
4
0
Order By: Relevance
“…Piper and Boote [59] showed variation in protein and fat concentration in 20 soybean cultivars, with protein content significantly dependent only on cultivar, while fat content on cultivar and temperature related to latitude. Further, other authors proved significant effect of genotype on protein [54], fat [55,60,61], ash [61], and carbohydrate (raffinose and stachyose) contents [62]. The results presented in this study showed little anecdotal varietal variation in sugar content, which is consistent with the study of Alsajri et al [55].…”
Section: Discussionsupporting
confidence: 91%
“…Piper and Boote [59] showed variation in protein and fat concentration in 20 soybean cultivars, with protein content significantly dependent only on cultivar, while fat content on cultivar and temperature related to latitude. Further, other authors proved significant effect of genotype on protein [54], fat [55,60,61], ash [61], and carbohydrate (raffinose and stachyose) contents [62]. The results presented in this study showed little anecdotal varietal variation in sugar content, which is consistent with the study of Alsajri et al [55].…”
Section: Discussionsupporting
confidence: 91%
“…The CV for oil content (1.63%) and protein content (1.56%) were of low magnitude indicating a higher experimental precision (Table 2). Nascimento et al (2010) observed CVs of 6.9 and 2.7% for oil and protein contents, respectively, in fifteen soybean cultivars. Although some authors have reported lower yields in off-season cultivated soybeans, the average grain yield of the UFUS soybean lines (2,698 kg/ha) at the four sites was similar to the national average (2,816 kg/ha) for the 2007/08 growing season.…”
Section: Resultsmentioning
confidence: 83%
“…During the final stages of evaluation and recommendation of cultivars for breeding programs, the study of adaptability and stability is essential to guide the breeder in the selection of the most appropriate genotypes (Cruz et al, 2012). Considering oil and protein traits in soybean, Nascimento et al (2010) emphasized the difficulty of recommending genotypes for different regions due to the paucity of studies of these characteristics under Brazilian conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Analysis of the variance of the mixed model for oil content in soybean genotypes indicates high statistical significance (p <0.01) of the effects of genotypes, environment and their interaction (Table 6). Environmental influence was predominant over influence of genotype and interaction G × E.Although oil content is a genetically determined trait and is considered a varietal characteristic, only 50% of the total variation in seed composition is the result of genotype (BRUMM and HURBURGH, 2002), while the rest of the variability is attributed to environmental factors, primarily temperature and humidity, as well as the interaction of genetic and agroecological factors (VOLLMANN et al, 2000a;NASCIMENTO et al, 2010;LAKIĆ et al, 2019;POPOVIĆ et al, 2013;. content of genotypes tested at the same location in different years were greater than the differences found in genotypes tested in the same year at different locations.…”
Section: Oil Contentmentioning
confidence: 99%